In vivo Overexpression of Electrogenic Sodium/Bicarbonate Cotransporter (NBCe1) by AAV9 Modifies the Cardiac Action Potential and the QT Interval in Mice - Di Mattía, Romina A.; Díaz Zegarra, Leandro A.; Valverde, Carlos A.; Blanco, Paula G.; Jaquenod De Giusti, Carolina; Portiansky, Enrique L.; Aiello, Ernesto A.; Orlowski, Alejandro (Frontiers in Cardiovascular Medicine, 2022)
Cardiac cells depend on specific sarcolemmal ion transporters to assure the correct intracellular pH regulation. The sodium/bicarbonate cotransporter (NBC) is one of the major alkalinizing mechanisms. In the heart two different NBC isoforms have been described: the electroneutral NBCn1 (1Na+:1HCO3-) and the electrogenic NBCe1 (1Na+:2HCO3-). NBCe1 generates an anionic repolarizing current that modulates the action potential duration (APD). In addition to regulating the pH, the NBC is a source of sodium influx. It has been postulated that NBC could play a role in the development of hypertrophy. The aim of this research was to study the contribution of NBCe1 in heart electrophysiology and in the development of heart hypertrophy in an in vivo mouse model with overexpression of NBCe1. Heart NBCe1 overexpression was achieved by a recombinant cardiotropic adeno-associated virus (AAV9) and was evidenced by western-blot and qPCR. AAV9-mCherry was used as a transduction control. NBCe1 overexpression fails to increase heart growth. Patch clamp and electrocardiogram were performed. We observed a reduction on both, ventricular myocytes APD and electrocardiogram QT interval corrected by cardiac rate, emphasizing for the first time NBCe1 relevance for the electrical activity of the heart.